The Analgesic Effect of Different Concentrations of Epidural Ropivacaine Alone or Combined With Sufentanil in Patients After Cesarean Section - Fangfang Miao; Kunpeng Feng; Xuexin Feng; Long Fan; Yu Lang; Qingfang Duan; Ruixue Hou; Di Jin; Tianlong Wang (Frontiers Media S.A., 2021)
Background: Patients experience moderate-high intensity postoperative pain after cesarean section (CS). The aim of this study was to investigate the optimal concentrations of ropivacaine and sufentanil for use in controlling pain after CS.Methods: One hundred and seventy-four women undergoing elective CS were randomly allocated to four groups. Epidural analgesia was administered with 0.1% ropivacaine in the R1 group, 0.15% ropivacaine in the R2 group, a combination of 0.1% ropivacaine and 0.5 μg/ml of sufentanil in the R1S group, and a combination of 0.15% ropivacaine and 0.5 μg/ml of sufentanil in the R2S group (at a basal rate of 4 ml/h, bolus dose of 4 ml/20 min as needed). Pain scores (numerical rating scale [NRS]: 0-10 cm) at rest (NRS-R), during movement (NRS-M), and when massaging the uterus (NRS-U) were documented at 6 and 24 h. We also recorded patient satisfaction scores, time to first flatus, motor deficits, and adverse drug reactions.Results: NRS (NRS-R, NRS-M, NRS-U) scores in the R2S group (2 [1-3], 4 [3-5], 6 [5-6], respectively) were lower than in the R1 group (3 [3-4], 5 [4-6], 7 [6-8], respectively) (p < 0.001, p < 0.05, p < 0.01, respectively) at 6 h; and patient satisfaction (9 [8-10]) was improved compared to the R1 group (8 [6-8]) (p < 0.01). The time to first flatus (18.7 ± 11.8 h) was reduced relative to the R1 group (25.9 ± 12.0 h) (p < 0.05). The time to first ambulation was not delayed (p > 0.05). However, the incidence of pruritus (4 [9.3%]) was increased compared to the R2 group (0 [0]) (p < 0.05) at 6 h, and the incidence of numbness (23 [53.5%], 23 [53.5%]) was increased compared to the R1 group (10 [23.3%], 10 [23.3%]) (all p < 0.01) at both 6 and 24 h.Conclusions: Although we observed a higher incidence of pruritus and numbness, co-administration of 0.15% ropivacaine and 0.5 μg/ml of sufentanil administered epidurally optimized pain relief after CS, with treated subjects exhibiting lower NRS scores, shorter time to first flatus, and higher patient-satisfaction scores.